HIV/AIDS prevention through peer education and support in secondary schools in South Africa - Maretha Visser (SAHARA-J, 2007)
The implementation and evaluation of a peer education and support programme in secondary schools to prevent and reduce high-risk sexual behaviour amongst adolescents is discussed. The aims of the programme were to provide accurate information about HIV/AIDS, discuss and reconsider peer group norms, and establish support for learners. In the programme that was implemented in 13 secondary schools in Tshwane, South Africa, peer educators were identified, trained and supported to implement the programme in their schools with the assistance of a teacher and postgraduate students as facilitators. Peer educators organised HIV awareness activities, facilitated class discussions on risk behaviour and gender relationships, and supported learners in solving personal problems. Process evaluation included weekly reports and focus group discussions with peer educators and teachers. A quasiexperimental design involving an experimental and control group, as well as pre- and post-assessments, was used to evaluate the impact of the programme on psychological well-being, personal control, school climate and reported high-risk behaviour of learners aged between 13 and 20 years. The results showed that the percentage of learners in the experimental group who were sexually experienced remained unchanged over the time period of 18 months. In contrast, a significantly increased percentage of learners in the control group were sexually experienced after the same time period. The control group also perceived more of their friends to be sexually experienced. No differences were reported in condom use in either of the groups. The findings of this study suggest that peer education can contribute to a delayed onset of sexual activity, and can therefore contribute to the prevention of HIV/AIDS amongst adolescents.